Challenges to the development of the trauma system in Egypt - Ahmed T. Hafez; Islam Omar; Mohamed Aly (AOSIS, 2023)
Trauma is a hidden disease in Egypt, and its significance on public health has been underestimated for decades. Road traffic accidents are the leading cause of injuries presented to hospitals in Egypt. Trauma systems in developed countries effectively reduced the morbidity and mortality associated with injuries in crowded cities. Developing a trauma system in Egypt is mandatory with the exploding population growth, increasing incidence of injuries, and the vast expansion of the infrastructures in the road network. However, the implementation of the trauma system in Egypt will not be devoid of challenges, including a lack of mandatory healthcare infrastructures such as adequate pre-hospital care, poor quality of data, and a shortage of adequately trained emergency physicians across the country.